Complete Disruption of All Nitric Oxide Synthase Genes Causes Markedly Accelerated Renal Lesion Formation Following Unilateral Ureteral Obstruction in Mice In Vivo - Naoya Morisada; Masayoshi Nomura; Hisae Nishii; Yumi Furuno; Mayuko Sakanashi; Ken Sabanai; Yumiko Toyohira; Susumu Ueno; Seiji Watanabe; Masahito Tamura; Tetsuro Matsumoto; Akihide Tanimoto; et al. (Elsevier, 2010)
Abstract.: The role of nitric oxide (NO) derived from all three NO synthases (NOSs) in renal lesion formation remains to be fully elucidated. We addressed this point in mice lacking all NOSs. Renal injury was induced by unilateral ureteral obstruction (UUO). UUO caused significant renal lesion formation (tubular apoptosis, interstitial fibrosis, and glomerulosclerosis) in wild-type, singly, and triply NOS−/− mice. However, the extents of renal lesion formation were markedly and most accelerated in the triply NOS−/− genotype. UUO also elicited the infiltration of inflammatory macrophages, up-regulation of transforming growth factor (TGF)-β1, and induction of epithelial mesenchymal transition (EMT) in all of the genotypes; however, the extents were again largest by far in the triply NOS−/− genotype. Importantly, long-term treatment with the angiotensin II type 1 (AT1)-receptor blocker olmesartan significantly prevented the exacerbation of those renal structural changes after UUO in the triply NOS−/− genotype, along with amelioration of the macrophage infiltration, TGF-β1 levels, and EMT. These results provide the first evidence that the complete disruption of all NOS genes results in markedly accelerated renal lesion formation in response to UUO in mice in vivo through the AT1-receptor pathway, demonstrating the critical renoprotective role of all NOSs-derived NO against pathological renal remodeling. Keywords:: nitric oxide synthase, renal remodeling, unilateral ureteral obstruction, knockout mouse, angiotensin